Moderasi Beragama di Kalangan Muslim Indonesia - Juhrianto Ardian Lutfhi; Try Sabella; Mofari jatul Fitriani (AL-Ikhtiar : Jurnal Studi Islam, 2024)
Religious moderation among Indonesian Muslims is an important concept in viewing, implementing and practicing religious teachings in an inclusive and progressive manner. The concept of religious moderation emphasizes the need to build attitudes that respect human dignity, promote tolerance, and strengthen harmony between religious communities. Challenges in implementing religious moderation include efforts to minimize violence against different beliefs, maintain plurality, and ensure the implementation of increasingly strong and collaborative religious moderation programs. With a focus on sustainable leadership and human resource development, religious moderation is expected to be the key to a Golden Indonesia 2045. The importance of a religious moderation perspective in building tolerance, harmony and shared prosperity in Indonesia is increasingly emphasized through various initiatives and regulations, such as Presidential Regulation Number 58 of the Year 2023 concerning Strengthening Religious Moderation. The research results show that religious moderation among Indonesian Muslims has a multidimensional meaning. Moderation is defined as a middle, balanced and tolerant attitude in understanding and understanding.. Abstrak Moderasi beragama di kalangan umat Islam Indonesia merupakan sebuah konsep penting dalam pengkajian, penerapan dan pengamalan ajaran agama secara inklusif dan progresif. Konsep moderasi beragama menekankan perlunya membangun sikap yang menghormati martabat kemanusiaan, mempromosikan toleransi, dan memperkuat kerukunan antar umat beragama. Tantangan dalam menerapkan moderasi beragama termasuk upaya untuk meminimalisir kekerasan terhadap kepercayaan yang berbeda, menjaga pluralitas, serta memastikan implementasi program-program moderasi beragama yang kian kuat dan kolaboratif. Dengan fokus pada keberlanjutan kepemimpinan dan pengembangan sumber daya manusia, moderasi beragama diharapkan menjadi kunci menuju Indonesia Emas 2045. Pentingnya perspektif moderasi beragama dalam membangun toleransi, kerukunan, dan kesejahteraan bersama di Indonesia semakin ditekankan melalui berbagai inisiatif dan regulasi, seperti arahan Eksekutif Nomor 58 Tahun 2023 yaitu tentang Penguatan Moderasi Beragama. Penelitian tersebut menunjukkan bahwasannya moderasi beragama di kalangan umat Islam Indonesia memiliki makna yang multidimensi. Moderasi diartikan sebagai sikap tengah, seimbang, dan toleran dalam memahami dan mengamalkan ajaran Islam. Implementasi moderasi beragama diwujudkan melalui berbagai pendekatan, seperti pendidikan agama, dialog antarumat beragama, dan pemberdayaan masyarakat.